Behind political ideas of welfare and productivity - Exploring ontological models and forms of exclusion - Pia Ringø; Maria Appel Nissen; Mia Arp Fallov; Rasmus Hoffmann Birk; Jens Kjærulff (Social Work and Society, 2018)
Political ideas of welfare, and social work, are based on shifting types of knowledge about man and society. Historically, welfare policies have aimed for inclusion, but have also marginalized 'the deviant', in the attempt to construct a common societal identity as 'the norm'. In this article we offer an analytical understanding and exploration of the historical construction of a social political narrative about how best to ensure a population consisting of 'productive individuals' and of how these narratives have led to shifting understandings, explanations and exclusions of knowledge of 'the uproductive individuals'. Through a historical analysis we identify the ontological models behind the political ideas of productivity which have been significant in the shaping of the Danish welfare state. These ontological models, underpinned by the prevailing forms of knowledge of the time, represent ideas and understandings of the generative mechanisms of social problems and have through history led to different welfare political efforts and restructurings of the content and function of social work. In the last part of the article, we question  how science and social work can contribute to the development of ontological models based on integrative, nuanced view on the dialectics between society, human beings and social problems in the future.